Clinical long-term and patient-reported outcomes of dental implants in oral cancer patients - Eik Schiegnitz; Lena Katharina Müller; Keyvan Sagheb; Lisa Theis; Vahide Cagiran; Peer W. Kämmerer; Joachim Wegener; Wilfried Wagner; Bilal Al-Nawas (SpringerOpen, 2021)
Abstract Background and purpose The aim of this clinical study was to investigate the clinical long-term and patient-reported outcome of dental implants in patients with oral cancer. In addition, analysis of the influence of radiation therapy, timing of implant insertion, and augmentation procedures on implant survival was performed. Material and methods This retrospective study investigated the clinical outcome of 711 dental implants in 164 oral cancer patients, inserted by experienced surgeons of the Department of Oral and Maxillofacial Surgery, University Medical Center Mainz, Germany. Oral health-related quality of life (OHRQoL) was evaluated. Results Cumulative 5-year and 10-year implant survival rates for all included implants were 87.3% and 80.0%. Implants placed straight after ablative surgery (primary implant placement) and implants placed after completing the oncologic treatment (secondary implant placement) showed a comparable implant survival (92.5% vs. 89.5%; p = 0.635). Irradiation therapy had no significant influence on implant survival of secondary placed implants (p = 0.929). However, regarding implant site (native bone vs. augmented bone) and radiation therapy (non-irradiated bone vs. irradiated bone), implants inserted in irradiated bone that received augmentation procedures showed a statistically significant lower implant survival (p < 0.001). Patients reported a distinct improvement in OHRQoL. Conclusions Promising long-term survival rates of dental implants in patients after treatment of oral cancer were seen. In addition, patients benefit in form of an improved OHRQoL. However, bone augmentation procedures in irradiated bone may result in an impaired implants' prognosis.